Sustainable Alternative Syngas Fuel [Working Title] 2019
DOI: 10.5772/intechopen.86236
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Effect of Water Gas Shift Reaction (Syngas) in Catalytic Upgrading of Heavy Crude Oil and Bitumen

Abstract: Industrial globalization and urbanization has placed man on a path for the quest of energy. Conspicuously there are various types and forms of energy with established technologies on harnessing and utilization wherein fossil fuel still remains the cheapest with straightforward application. Although, conventional fossil fuel resources are depleting because of population growth, unconventional reservoirs are exploited daily with limited production due to inadequate and expensive technology making them stand at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The thermal conversion of hydrocarbons in the superheated steam medium (at 500-700 • C) can have a number of environmental and technological advantages, such as the neutralization of harmful compounds formed in the steam-gas mixture [17,18] and the improvement of the quality indicators of the condensed liquid hydrocarbons (reduced content of sulfur compounds, ash, changed molecular weight of light hydrocarbons) [19]. In addition, the use of superheated steam as a hydrocarbons conversion agent increases the H 2 content in the resulting synthesis gas: C + H 2 O → CO + H 2 , CH 4 + H 2 O → CO + 3H 2 and CO + H 2 O → CO 2 + H 2 [20][21][22][23]. Efika et al [24] reported that the use of steam as an additional agent for biomass conversion increases the hydrogen concentration in the composition of gas-phase products by 30%.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conversion of hydrocarbons in the superheated steam medium (at 500-700 • C) can have a number of environmental and technological advantages, such as the neutralization of harmful compounds formed in the steam-gas mixture [17,18] and the improvement of the quality indicators of the condensed liquid hydrocarbons (reduced content of sulfur compounds, ash, changed molecular weight of light hydrocarbons) [19]. In addition, the use of superheated steam as a hydrocarbons conversion agent increases the H 2 content in the resulting synthesis gas: C + H 2 O → CO + H 2 , CH 4 + H 2 O → CO + 3H 2 and CO + H 2 O → CO 2 + H 2 [20][21][22][23]. Efika et al [24] reported that the use of steam as an additional agent for biomass conversion increases the hydrogen concentration in the composition of gas-phase products by 30%.…”
Section: Introductionmentioning
confidence: 99%